Aesthetic and Psychological Features of Irony - Mavlyanova Ugiloy Khamdamovna (International Journal on Integrated Education, 2021)
The relevance of the study of irony is related to the need to develop comics, especially its value and psychological aspects. The irony is described as a kind of comic, and in this respect it serves as an emotional, valuable, aesthetic relationship. At the same time, the content of the irony is often overlooked as a form, with its specific features disappearing as an emotionally-valued relationship. However, while much of the historical, philosophical, and functional aspects of irony have been studied, its expressive features, experimental value, and psychological aspects, which seem to be important for understanding the essence of irony, have not been sufficiently studied.